The antimicrobial susceptibility of ornithobacterium rhinotracheale isolates - Osman Erganiş; H. Hüseyin Hadimli; Kürşat Kav; Zafer Sayın (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the study was to determine susceptibility of Ornithobacterium rhinotracheale isolates to antibiotics from layers, broilers and turkeys. Materials and Methods: The total of 28 isolates (2 layer pullets, 5 broilers, 21 turkeys and 2 standard strains) of O. rhinotracheale were tested. Eighteen antimicrobial discs (penicillin, ampicillin, amoxicillin, amoxicillin + clavulanic acid, oxytetracycline, enrofloxacin, ciprofloxacin, danofloxacin, norfloxacin, trimethoprim + sulfamethoxazole, clarithromycin, lincomycin, clindamycin, erythromycin, spiramycin, gentamicin, neomycin and streptomycin) were used to determine the susceptibility of O. rhinotracheale isolates to antimicrobials. Results: While all O. rhinotracheale isolates (100%) were susceptible to ampicillin, amoxicillin and ciprofloxacin, all of O. rhinotracheale isolates (100%) were resistant to gentamicin, streptomycin and trimethoprim + sulfamethoxazole. Conclusion: In the treatment of O. rhinotracheale infections firstly antibiotic sensitivity should be determined.